PERANAN VISUM ET REPERTUM PSIKIATRIKUM GUNA PERTIMBANGAN HAKIM TERHADAP PELAKU TINDAK PIDANA YANG SAKIT JIWA DALAM PROSES PERADILAN (STUDI DI RUMAH SAKIT JIWA DAERAH PROVINSI KEPULAUAN BANGKA BELITUNG) - Yang Meliana (Justici, 2020)
ABSTRACT Visum et repertum psychiatricum need to be made in respect of the Article 44 (1) of the Criminal Code, which reads: "Whoever does something which can’t be accounted to him due to his soul defects in growth or impaired due to illness, was not convicted". According to R. Suparmono, post mortem psychiatricum intended as a series of rules of evidence about the quality of the suspect at the time of committing the criminal and responsible for determining the ability of the suspect. Forensic psychiatry it serves as an expert witness, as a legal expert helpers to collect data that can be used in making legal decisions. Post mortem psychiatricum serves as an expert witness, assistant legal experts to collect data that can be used in making legal decisions. While the purpose of the post mortem psychiatricum, giving reality (evidence) to judge, concluded based on causal relations, allowing the judge to call other specialists to make conclusions newer ver. Seeing the need for a mental health professional medical help for judges in criminal proceedings, the written statement in the form of a post mortem psikiatricum made by the physician of the soul, then the judge can determine the extent of the defendant's ability to be responsible when committing a crime. So the doctor describe the mental state of the accused is (descriptive), while the judge is a judge (normative). Before doctors psychiatrists provide written statement in the form of a Visum et repertum psychiatricum, first he, in this case the doctor psychologists observe the patient, in this case is the defendant. While the factors that hinder a doctor psychiatrist to give a post mortem examination psikiatricum in criminal cases, constraints encountered physicians in making a post mortem psychiatricum is a communication problem, and the questions in the application letter Visum mortem psychiatricum are not clear. Constraints faced by judges in the use of post mortem psychiatricum is the strength of evidence Visum mortem psychiatricum that can not bind the judge, and about language and medical terms contained in a post mortem Psikiatrikum vague so as not to be understood by the judge Visum et repertum psychiatricum grounded in absolute theory or the theory of retaliation (vergeldings Theorien) which is the basis of the justification for the imposition of penal suffering form it on criminals. State reserves the right to impose punishment for the criminals have to attack and rape on the rights and legal interests are protected. By Visum et repertum psychiatricum and information that has been given by a psychiatrist orally and in writing at the hearing, have an influence for the judge to add confidence that the defendant actually mentally ill, and in the end the judge ruled that the defendant found not mentally ill defendant must account for his actions.